2020
DOI: 10.1080/09168451.2020.1763155
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis is involved in alcohol-induced cell death in vivo and in vitro

Abstract: A critical pathogenic factor in the development of lethal liver failure is cell death induced by the accumulation of lipid reactive oxygen species. In this study, we discovered and illuminated a new mechanism that led to alcoholic liver disease via ferroptosis, an iron-dependent regulated cell death. Study in vitro showed that both necroptosis inhibitor and ferroptosis inhibitors performed significantly protective effect on alcohol-induced cell death, while apoptosis inhibitor and autophagy inhibitor had no su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…Although there is a growing consensus that lipid disorder and hepatic iron overload are prevalent features of ALD [ 72 ], only in recent years have researchers began taking ferroptosis’ role in alcoholic liver damage into consideration. During the repair of ethanol-induced liver damage, ferroptosis is always negatively regulated [ 73 , 74 ]. Alcohol treatment results in massive ROS accumulation and lipid peroxidation both in cell culture and in mouse models of ALD, which could be rescued by a ferroptosis inhibitor [ 74 ].…”
Section: The Involvement Of Ferroptosis In Typical Liver Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is a growing consensus that lipid disorder and hepatic iron overload are prevalent features of ALD [ 72 ], only in recent years have researchers began taking ferroptosis’ role in alcoholic liver damage into consideration. During the repair of ethanol-induced liver damage, ferroptosis is always negatively regulated [ 73 , 74 ]. Alcohol treatment results in massive ROS accumulation and lipid peroxidation both in cell culture and in mouse models of ALD, which could be rescued by a ferroptosis inhibitor [ 74 ].…”
Section: The Involvement Of Ferroptosis In Typical Liver Diseasesmentioning
confidence: 99%
“…During the repair of ethanol-induced liver damage, ferroptosis is always negatively regulated [ 73 , 74 ]. Alcohol treatment results in massive ROS accumulation and lipid peroxidation both in cell culture and in mouse models of ALD, which could be rescued by a ferroptosis inhibitor [ 74 ]. Similarly, some investigations found that dimethyl fumarate has a protective effect on ethanol-induced oxidative injury through activating the Nrf2 pathway and repressing ferroptosis [ 73 ].…”
Section: The Involvement Of Ferroptosis In Typical Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Fer-1 is a recognized inhibitor of ferroptosis which can reduce PUFAs in membrane oxidation [ 8 ]. By inhibiting hepatocyte ferroptosis, Fer-1 improves liver damage mediated by ALD, NAFLD, and hepatic ischemia/reperfusion (I/R) injury [ 29 , 76 , 99 ] ( Table 1 ). With in-depth exploration of this field, recent research has solved the long-standing Fer-1 anti-ferroptosis paradox.…”
Section: Drugs Targeting Ferroptosis In Liver Diseasesmentioning
confidence: 99%
“…A second parallel protective pathway also exist, which involves the oxidoreductase FSP1/AIFM2 by generating a potent lipophilic antioxidant to suppresses the propagation of lipid peroxides (63,64). Hepatic ferroptosis has been found in the liver of animal models of alcoholic liver disease (ALD), nonalcoholic steatohepatitis, acetaminophen induced hepatotoxicity, and viral hepatitis (65)(66)(67)(68). However, it remains to be determined whether bile acids cause hepatocyte ferroptosis during cholestasis.…”
Section: Cholestatic Levels Of Bile Acids Injure Hepatocytesmentioning
confidence: 99%